2019
DOI: 10.1002/jor.24514
|View full text |Cite
|
Sign up to set email alerts
|

COMP in the Infrapatellar Fat Pad—Results of a Prospective Histological, Immunohistological, and Biochemical Case–Control Study

Abstract: Knee osteoarthritis (OA) involves several structures and molecules in the joint, which interact in a pathophysiological process. One of these molecules is the cartilage oligomeric matrix protein (COMP). Elevated COMP levels in the synovial fluid as well as in the serum have been described in OA patients. However, this has not been described in the infrapatellar fat pad (IPFP) tissue before. In this prospective trial, we collected 14 IPFPs from patients with high‐grade OA (mean age 63.8 ± 17.6 years) who underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Two studies were identified for infrapatellar fat pad [30,31]. Grevenstein et al (2020) showed no change in COMP content between OA and control fat pads [30] and Belluzzi et al (2020) showed that there was a decrease in collagen I and III expression in OA fat pads compared to controls [31].…”
Section: Fat Pad In Human Oamentioning
confidence: 99%
“…Two studies were identified for infrapatellar fat pad [30,31]. Grevenstein et al (2020) showed no change in COMP content between OA and control fat pads [30] and Belluzzi et al (2020) showed that there was a decrease in collagen I and III expression in OA fat pads compared to controls [31].…”
Section: Fat Pad In Human Oamentioning
confidence: 99%
“…The expression levels were detected using the TAlink mouse/rabbit polymer detection system (TAHC04D, BioTnA Biotech, Kaohsiung, Taiwan). A semi-quantitative method was used to score cytokine expression in all tissue sections, as previously described [27]. Briefly, Figure 2 shows the cytokines expressed in sections that were analyzed regarding staining intensity using a score from 0 to 3 (0 = no staining, 1 = weak staining, 2 = moderate staining, 3 = strong staining).…”
Section: Immunohistochemical Staining and Scoring Systemmentioning
confidence: 99%